Highly electrically conductive layered carbon derived from polydopamine and its functions in SnO2-based lithium ion battery anodes - Kong, Junhua (2013)
Thin carbonized polydopamine (C-PDA) coatings are found to have similar structures and electrical conductivities to those of multilayered graphene doped with heteroatoms. Greatly enhanced electrochemical properties are achieved with C-PDA-coated SnO2 nanoparticles where the coating functions as a mechanical buffer layer and conducting bridge.